Nation Building and Social Values in Nepal - Tara Nath Ghimire; Amrit Kumar Shrestha; Shyam Prasad Phuyel (Randwick International of Social Science Journal, 2021)
Social norms play an important role in the state-building process. If the time of formation of Nepal is considered as the period of unification, then some important facts regarding the formation of the state of Nepal and the structure of the society here can be recounted. Regarding the formation of the nation-state, the structure of the Nepali state, and the position of the Nepali society are not of the same nature. From the pre-unification states of Limbuwan, Khumbuwan, Kirat, Khas, Baisi, Chaubisi, Shen, etc. to the restructuring period of the state, the state structure has not been formed in the recognition of the nation-state. Because the small and big states before unification were states built on power. Due to power, the great form of the Gurkha state had built a unitary Nepal. There is not general recognition of the state-building process of the nation-state. In the same way, even when restructuring the state, that recognition was not accepted. The foundations of federal-state formation, such as language, religion, and the basis of equality and plurality of the population, were also not accepted, which is a form of recognition of the nation-state. In such a situation, this article attempts to study a state-building and social tradition which is already coming together in Nepali society